Effects in Adherent Subjects. (3rd July 2018) - Permutt, Thomas
ABSTRACT: Dropouts confound the treatment effect when the outcome and the dropout process both depend on subject characteristics. If dropout is unrelated to treatment, there is an unconfounded effect, but it is the effect in a principal stratum, rather than a de jure effect. There are at least two different definitions of the effect if all subjects adhered, giving effects different numerically from each other and from the effect in the adherent principal stratum. Estimation of either of these two effects requires an assumption (MAR) different from but sometimes confused with the assumption that dropout is unrelated to treatment.